Differential contributions of nuclear lamina association and genome compartmentalization to gene regulation. Issue 1 (31st December 2023) - Das, Priyojit; San Martin, Rebeca; McCord, Rachel Patton
ABSTRACT: Chromatin regions that interact with the nuclear lamina are often heterochromatic, repressed in gene expression, and in the spatial B compartment. However, exceptions to this trend allow us to examine the relative impact of lamin association and spatial compartment on gene regulation. Here, we compared lamin association, gene expression, Hi-C, and histone mark datasets from cell lines representing different states of differentiation across different cell-type lineages. With these data, we compare, for example, gene expression differences when a B compartment region is associated with the nuclear lamina in one cell type but not in another. In general, we observed an additive rather than redundant effect of lamin association and compartment status. But, whether compartment status or lamin association had a dominant influence on gene expression varied by cell type. Finally, we identified how compartment and lamin association influence the likelihood of gene induction or repression in response to physicochemical treatment.